Optimization of the process modules for a top-down silicon nanowire fabrication using optical lithography and orientation dependent etching - Za'bah, Nor Farahidah; Kwa, Kelvin S. K.; O'Neill, Anthony (Trans Tech Publications, Switzerland, 2013)
A top-down silicon nanowire fabrication using a combination of optical lithography and orientation dependent etching has been developed using Silicon-on Insulator (SOI) as the starting substrate. The design of experiments for the optimization of the process flow especially on the orientation dependent etching using potassium hydroxide (KOH) and Tetra-Methyl Ammonium Hydroxide (TMAH) are presented in this paper. Based on the etching experiments using silicon substrates, KOH with added isopropyl alcohol (IPA) had shown to have a consistent etch rate with acceptable silicon surface roughness as compared with its other counterparts. The concern regarding the effect of line edge roughness (LER) as a result of optical lithography was highlighted and, therefore, the optimization of the patterning procedure was also discussed and presented.